Negative Brand Experiences and Purchase Intention of Green Wall Coating Brands: The Mediating Effect of Brand Identity - Zhu, Kongliang (Community and Social Development Journal, 2024)
The purpose of this study was 1) to explore the impact of consumers’ negative experiences with green wall coating brands on the brand identity of wall paint, 2) to analyze the effects of brand identity with green wall coating brands on purchase intentions, and 3) to test the mediating effect of green brand identity. Utilizing a quantitative research approach and simple random sampling technique, this study engaged 402 Chinese respondents aged 18 and older, all of whom had relevant purchase experiences with green wall coating products. The data collected were subjected to Confirmatory Factor Analysis (CFA) and Structural Equation Modeling (SEM) to assess model fit, as well as to establish the validity and reliability of the variables used in the study. The findings of this research revealed that all four dimensions of negative brand experience, which include negative functional experience (β =-0.189), negative emotional experience (β=-0.308), negative cognitive experience (β=-0.444), and negative social value experience (β=-0.134), have a negative impact on green brand identity. Additionally, the study confirmed a positive relationship between green brand identity and the intention to purchase green wall coating brands (β=0.655). Finally, the study established that green brand identity acts as a partial mediator between negative brand experiences (negative functional experience, negative emotional experience, negative cognitive experience, and social value negative experience) and the purchase intention of green wall coating brands (β3a=-0.124; β3b=-0.054; β3c=-0.126; β3d=-0.050). In light of these findings, this research provides specific and practical recommendations and improvement strategies for businesses within the green wall coating industry. These insights are aimed at enhancing their services and bolstering their competitive advantage.